Survival of Patients with CML on Imatinib Experience with 44 Iraqi Patients - Jawad, Ali M.; Yassin, Batool A.G.; Salman, Nabeel; Al-Ameri, Ali (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Chronic myeloid leukemia (CML) is a clonal stem disease with distinctive clinical course which is ultimately fatal. It is characterized by the presence of Philadelphia chromosome (t 9:22).Tyrosine kinase inhibitors like imatinib mesylate as targeted therapy had revolutionized the management of CML with significant prolongation of overall survival and decreased rate of blastic transformation. Objective:This study will describe the experience of treating 44 Iraqi patients with chronic myeloid leukemia by imatinib at the National Hematology Centre in Baghdad. Patients and Methods:This study included 44 Iraqi patients diagnosed in Chronic phase CML at the National Centre of Hematology in Baghdad from February 2003 till January 2006, all were pretreated with alfa interferon and hydroxyurea. All patients were started on imatinib mesylate 400 mg orally daily. The end points included overall survival (OS) and Blastic transformation free survival (TFS).The effect of age, gender, WBC count on starting Imatinib, presence of splenomegaly and duration of diagnosis of CML prior to starting imatinib, on the OS and TFS were studied. Results:Median age was 35 years with 27 males and 17 females. The 3 year OS was 88.6% and the TFS was 79.5%.The only factor that had negative impact on OS and TFS was a diagnosis of CML more than 2 years before starting imatinib. The most common side effects were myalgia(75%) and peripheral oedema(65%). Neutropenia(20%),thrombocytopenia(12%) and elevated serum transaminases (2%) necessitated temporary cessation of treatment.No cytogenetic and molecular studies were available . Conclusion:Imatinib is an effective therapy for Iraqi patients with CML with tolerable side effects and should be offered to newly dignosed CML patients as early as possible as frontline therapy to ensure better OS and TFS.Establishment of cytogenetic and molecular studies are crucial to optimize management.